Formation of service and resource stability conditions of urban public passenger transport - Вдовиченко, Володимир Олексійович (Technology audit and production reserves, 2016)
Service and resource parameters of urban public passenger transport operation are dominant for formation of its sustainability from the standpoint of internal and external processes. The sustainability of urban public passenger transport reflects its properties to keep under the influence of internal and external influences for a long time, which is correlated with time and changing the system, processes of its homeostatic equilibrium state, structure, nature of operation and to ensure the effective functioning of the urban environment. Its sustainability is achieved by forming reaction responses to influence, which aims to compensate their negative impact. The source of the formation of such compensatory actions is reserves of its internal (transport resources) and external resources (transport network resources). Formation of compensatory actions to influence must provide the appropriate level of its operation results of urban public passenger transport. Synthesis of the requirement to provide compensation of resource needs and performance characteristics helps to define the conditions for achieving sustainability of functional processes of urban public passenger transport. The form of the boundaries of acceptable sustainability parameters of urban public passenger transport is revealed from the standpoint of service and resource characteristics of its operation. The sustainability scheme of functional processes of urban public passenger transport is reflected conditions and principles of sustainable development of urban environments and allows to assess sustainability degree using an available form of their accounting.